Impact of Phytochemicals on Managing Chronic Brain Disorders: Exploring Therapeutic Potential - Trivedi, Dr. Rahul (Asian Journal of Pharmaceutics (AJP), 2024)
Numerous neuropsychiatric such as anxiety and depression as well as neurodegenerative conditions such as dementia and Alzheimer’s disease (AD) are primarily emerging in contemporary times as a result of stressful lifestyles. Presently approved pharmacological interventions for the majority of chronic brain disorders appear to address symptoms only, lacking significant disease-modifying effects. The use of synthetic drugs in the treatment is also associated with serious and life-threatening side effects. At present, there has been a notable surge in research investigating phytochemicals as substitutes for primary conventional antipsychotic and memoryenhancing medications. Phytochemicals sourced from herbal plants take part in a crucial role in conserving the chemical equilibrium of the brain further they are effective in protecting from neurodegeneration, preventing the progress of neurological disorders as well as improving the condition of depression and anxiety. In this study, we mainly focus on highlighting the therapeutic potential of phytochemicals in neuroprotection, dementia, AD, and depression. In addition, an attempt to list out the phytochemicals used in the management of chronic brain disorders has been made.